Releb'al Q'ij = Donde nace el sol - Sajcabun, Edgar; Simón, Priscila (Casa Comal, 2012)
It tells the story of the Mayan people, based on four stories that allude to the important moments of the millenary culture. One of the stories is that of Maya, who witnesses the invasion of their ancestral culture and must flee to save her life. The nomadic life will be a constant for her, and on the way she knows the suffering of her people, due to the lack of land and the foreign invasion. --